The extracellular matrix an overview - Mecham, Robert P.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Knowledge of the extracellular matrix (ECM) is essential to understand cellular differentiation, tissue development, and tissue remodeling. This volume of the series Biology of Extracellular Matrix provides a timely overview of the structure, regulation, and function of the major macromolecules that make up the extracellular matrix. It covers topics such as collagen types and assembly of collagen-containing suprastructures, basement membrane, fibronectin and other cell-adhesive glycoproteins, proteoglycans, microfibrils, elastin, fibulins and matricellular proteins, such as thrombospondin. It also explores the concept that ECM components together with their cell surface receptors can be viewed as intricate nano-devices that allow cells to physically organize their 3-D-environment. Further, the role of the ECM in human disease and pathogenesis is discussed as well as the use of model organisms in elucidating ECM function.
An overview of extracellular matrix structure and function -- Fibronectin and other adhesive glycoproteins -- Collagen: suprastructures and collagen fibril assembly.- Asement membrane; Hyaluronan and the Aggregating Proteoglycans -- The small, leucine-rich proteoglycans -- Microfibrils and fibrillin -- Elastin -- Lysyl oxidase and lysyl oxidase-like enzymes -- The Fibulins -- Matricellular proteins.
Electronic reproduction.
Keywords: Extracellular matrix; Electronic books